Новые породы и виды палеарктических андрен (Hymenoptera, Andrenidae). Сообщение 2 - Осычнюк, А.3. (Вестник зоологии, 1993)
A new Andrena F. subgenus Calcarina is established to include 2 Middle Asian species: A. cochlearicalcar and A. laticalcar. 5 species are described as new: Andrena (Poliandrena) kryzhanovskii sp. n., A. (Truncandrena) zlatae sp. n., A. (A.) valentinae sp. n., (Midlle Asia), A. Holandrena) labiatula sp. n. (Crimea), A. (Euan-drena) khosrovi sp. n. (Transcaucasia). Type material is deposited in Institiute of Zoology, Ukrainian Academy of Sciences (Kiev), Zoological Institute, Russian Academy of Sciences (St.-Petersburg), Zoological Museum, Moscow University.